ISOLATION AND MODIFICATION OF CELLULOSE FROM RAJA NANGKA BANANA STEMS FOR ADSORPTION OF METHYL ORANGE - Ayu Puspita Ningratri, Wanda
The textile industry is one of the fastest growing industries in Indonesia. One of the most widely used dyes in the textile industry is methyl orange. Methyl orange is a substance that is carcinogenic. On of the method to overcome the problems, related to waste water containing methyk orange is adsorption. Adsorption has advantages as it is effective and low cost. The adsorption method in this study used an adsorbent from a natural polymer, namely cellulose derived from Raja Nangka banana stemS. To increase the performance of cellulose in the adsorption processof methyl orange, a modification was made through the graft copolymerization method using 2-(dimethylamino)ethyl acrylate (DMAEA) as a monomer and cerium (IV) ammonium nitrate as a initiator. The resulting product is cellulose-gpoly(DMAEA). This research involved cellulose isolation, cellulose modification, characterization of the resulting polymers, adsorption, and desorption studies. In the cellulose isolation process, a yield of 25% (w/w) was obtained. The percentage of cellulose grafting obtained was 90% and the yield percentage was 40% (w/w). These results were obtained for a theoretical degree of polymerization (DPn) of 10, with a theretical percent modification of sugar residues of 50% and a polymerization temperature of 75o C. The FTIR data showed that there were peaks at wave numbers 1303,4 cm?1 and 1726,1 cm?1 which came from the C-N and C=O functional groups. These data showed that cellulose-g-poly(DMAEA) was successfully synthesized. X-ray diffraction data showed a new peak of cellulose-gpoly(DMAEA) at 2? of 47,4o and 56,4o . The adsorption kinetics study showed that the adsorption follow a pseudo-second order kinetic model. In addition, the adsorption data showed that the optimum pH for cellulose and cellulose-g-poly(DMAEA) was pH 3, while the optimum contact time for cellulose was 105 minutes and cellulose-g-poly(DMAEA) was 45 minutes. Furthermore, the adsorption efficiency value for cellulose was 88,7% and for cellulose-g-poly(DMAEA) was 74,4%. The average desorption efficiency using NaOH solution with a concentration of 1 M for cellulose was 80% and for cellulose-g-poly(DMAEA) was 76,2%. This showed that methyl orange was easy to be desorbed from the adsorbent using an alkaline solution and indication that the process was physical adsorption.